Color image encryption system using combination of robust chaos and chaotic order fractional Hartley transformation - Gurpreet Kaur; Rekha Agarwal; Vinod Patidar (Journal of King Saud University: Computer and Information Sciences, 2022)
The paper proposes a robust color image encryption scheme based on a real fractional Hartley transform with chaotic transform orders. The multilayer scheme comprises of a PWLCM (piecewise linear chaotic map) based circular blending of color components, PWNCA (piecewise nonlinear chaotic map) based nonlinear processing in spatial domain followed by a multiple chaotic order fractional Hartley transform to obtain encrypted image. The input parameters for chaotic mapping used in each encryption stage serve as secret keys. A reality preserving transform enables to eliminate the complexity issues of transform. The proposed scheme not only overcomes the limitation of linearity in transform orders of multiparameter scheme but also the vulnerability of transform to information leakage. Besides this, the use of multilayer security has led to larger key space. Results and analysis substantiate the fact that proposed scheme is robust, highly sensitive and shows considerably better performance than other similar-state-of-art schemes.